Multi-Dimensional Impact of Cyber Gender-Based Violence: Examining Physical, Mental, Social, Cultural, and Economic Consequences - Nadhiroh, A’im Matun; Winarti, Eko; Rozifa, Annisa’ Wigati; Saudah, Noer (Gaceta Médica de Caracas, 2023)
Background: The Internet, especially social media, is also at risk of being misused and triggering violence against humans. Gender-based violence (GBV) facilitated by new technologies is a phenomenon that increasingly affects the privacy and safety of women and girls in and out of cyberspace. This study aimed to describe the physical, mental, social, cultural, and economic impacts of gender-based violence of cyber. Methods: This study used a descriptive survey. The population of this study was adolescents in the East Java region; the sample size was 480 adolescents selected using a purposive sampling technique, with the following criteria: adolescents aged 12-25 years and willing to be respondents.